1995
DOI: 10.1042/bj3050211
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human mucin gene MUC5AC: a consensus cysteine-rich domain for 11p15 mucin genes?

Abstract: To date five human mucin cDNAs (MUC2, 5A, 5B, 5C and 6) mapped to 11p15.3-15.5, so it appears that this chromosome region might contain several distinct gene loci for mucins. Three of these cDNAs, MUC5A, B and C, were cloned in our laboratory and previously published. A common number, 5, was recommended by the Human Gene Mapping Nomenclature Committee to designate them because of their common provenance from human tracheobronchial mucosa. In order to define whether they are products of the same gene locus or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(88 citation statements)
references
References 47 publications
0
87
0
1
Order By: Relevance
“…Terminus-Based on the 99% sequence identity between MUC5AC clone JUL 32 (19) and HGM-1 nucleotides 1947-2278 (1), we hypothesized that HGM-1 is a part of MUC5AC. Based on Ͼ60% similarity between HGM-1 and the amino-terminal cysteine-rich domain of MUC2 (D-domain 3), we hypothesized that HGM-1 is an amino-terminal sequence.…”
Section: Race-pcr Cdna Cloning and Sequence Determination Of The Mucmentioning
confidence: 99%
See 2 more Smart Citations
“…Terminus-Based on the 99% sequence identity between MUC5AC clone JUL 32 (19) and HGM-1 nucleotides 1947-2278 (1), we hypothesized that HGM-1 is a part of MUC5AC. Based on Ͼ60% similarity between HGM-1 and the amino-terminal cysteine-rich domain of MUC2 (D-domain 3), we hypothesized that HGM-1 is an amino-terminal sequence.…”
Section: Race-pcr Cdna Cloning and Sequence Determination Of The Mucmentioning
confidence: 99%
“…Northern Blot Analysis of Tissue Distribution of RNA Corresponding to Newly Cloned Sequence-Our interpretation that the 5Ј extension of HGM-1 (MUC5AC-5ЈRP) is at the 5Ј-end of MUC5AC rests primarily on the 99% similarity between a portion of HGM-1 and the MUC5AC cDNA JUL 32 (19). Further confirmation of the identity between our new sequence and MUC5AC was provided by Northern blot analysis in which we observed that a probe from our new sequence showed tissuespecific hybridization identical to that obtained using a probe from the previously described MUC5AC C-terminal cDNA NP3a (8) (Fig.…”
Section: Race-pcr Cdna Cloning and Sequence Determination Of The Mucmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult rats (8 weeks after birth) served as controls. Five doses of hydrocortisone (1,5,10,25, 50 mg/kg) and vehicle (olive oil) were subcutaneously injected into the 5-d-old rats. After 2 d (7-d-old), the animals were sacrificed under ether anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…The cDNAs of the human mucin core peptides have been partially or fully cloned, and MUC1-8 has been detected in various organs. [1][2][3][4][5][6][7][8][9] Mucins are classified according to their biochemical characteristics as membrane-associated and secreted types. The secreted mucins are further classified as gel-forming and soluble types.…”
mentioning
confidence: 99%